Quasi-matter bounce and inflation in the light of the CSL model - Leon Garcia, Gabriel (2016)
The Continuous Spontaneous Localization (CSL) model has been proposed as apossible solution to the quantum measurement problem by modifying theSchr"odinger equation. In this work, we apply the CSL model to twocosmological models of the early Universe: the matter bounce scenario and slowroll inflation. In particular, we focus on the generation of the classicalprimordial inhomogeneities and anisotropies that arise from the dynamicalevolution, provided by the CSL mechanism, of the quantum state associated tothe quantum fields. In each case, we obtained a prediction for the shape andthe parameters characterizing the primordial spectra (scalar and tensor), i.e.the amplitude, the spectral index and the tensor-to-scalar ratio. We found thatthere exist CSL parameter values, allowed by other non-cosmologicalexperiments, for which our predictions for the angular power spectrum of theCMB temperature anisotropy are consistent with the best fit canonical model tothe latest data released by the Planck Collaboration.